1999
DOI: 10.1097/00005373-199902000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tissue Oxygenation during Hemorrhagic Shock, Resuscitation, and Alterations in Ventilation

Abstract: Directly measured PbrO2 was highly responsive to changes in FiO2, ventilatory rate, and blood volume in this experimental model. In particular, hypoventilation significantly increased PbrO2, whereas hyperventilation had the opposite effect. The postresuscitation increase in PbrO2 may reflect changes in both O2 delivery and O2 metabolism. These experiments set the stage for future investigations of a variety of resuscitation protocols in both normal and injured brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 30 publications
7
39
2
Order By: Relevance
“…Changes in ventilation provided an increase in P btO 2 in the setting of hypoventilation and a decrease in P btO 2 with hyperventilation. 45 Hyperventilation exacerbated the decrease in P btO 2 during experimental hemorrhagic shock. 46 These studies, while showing the feasibility of P btO 2 monitoring, also demonstrated the ill effects of hyperventilation, which had been used as a standard treatment for patients with increased intracranial pressure.…”
Section: Validation Of Cerebral Oxygen Monitoringmentioning
confidence: 94%
See 1 more Smart Citation
“…Changes in ventilation provided an increase in P btO 2 in the setting of hypoventilation and a decrease in P btO 2 with hyperventilation. 45 Hyperventilation exacerbated the decrease in P btO 2 during experimental hemorrhagic shock. 46 These studies, while showing the feasibility of P btO 2 monitoring, also demonstrated the ill effects of hyperventilation, which had been used as a standard treatment for patients with increased intracranial pressure.…”
Section: Validation Of Cerebral Oxygen Monitoringmentioning
confidence: 94%
“…In a series of normal cats, Zauner et al 44 demonstrated a mean P btO 2 of 42 mm Hg, which decreased by 29% with hyperventilation. Manley et al 45 showed that changes in brain tissue oxygen coincided with the physiological shifts that occur during hemorrhagic shock. Using a swine model, they demonstrated that a decrease in P btO 2 was seen with hemorrhage and recovered with resuscitation.…”
Section: Validation Of Cerebral Oxygen Monitoringmentioning
confidence: 99%
“…Previous experiments in our laboratory using computerized tomography as well as necropsy with gross examination of in-situ brain probes following brain removal have confirmed correct ana- tomic placement using this technique. [19][20][21] A fiberoptic pressure transducer (Camino Laboratories, San Diego, CA) was placed in a 2-mm burr hole 5 mm caudal to the right coronal suture for continuous monitoring of intracranial pressure (ICP). A midline burr hole was placed anterior to the bregma for introduction of a 4-Fr catheter used for collection of venous sagittal sinus blood to monitor cerebral venous oxygen tension (PcvO 2 ) and saturation (ScvO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The in-vivo response of the brain oxygen probes was evaluated by increasing the FiO 2 to 1.0, after which an increase in PbrO 2 was observed that was consistent with previous studies. [19][20][21] Once the response to 1.0 oxygen was validated, the FiO 2 was decreased to 0.3 and swine were allowed to stabilize for another 30 minutes. At the completion of each experiment, probes were placed in their respective calibration barrels and observed for return to the calibrated oxygen levels recorded before the experiment began.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation